L'art des Etats-Unis - Butor, Michel; Martin, Jennifer; Massu, Claude; Nichols, Sarah; Parigoris, Alexandra; Riout, Denys; Travis, David (Paris : Editions Citadelles & Mazenod Paris, 1992)
Aalto, Alvar ; Adams, Robert ; Andre, Carl ; Arbus, Diane ; Autio, Rudy ; Baldessari, John ; Baltz, Lewis ; Barnes, Edward L. ; Barry, Robert ; Basquiat, Jean-Michel ; Baziotes, William ; Belluschi, Pietro ; Berman, Zeke ; Bluemner, Oscar Julius ; Borofsky, Jonathan ; Bourgeois, Louise ; Breuer, Marcel ; Bruce, Patrick Henry ; Bunshaft, Gordon ; Calder, Alexander ; Callahan, Harry ; Caponigro, Paul ; De Carava, Roy ; Chamberlain, John ; Chihuly, Dale ; Christo ; Close, Chuck ; Crawford, Ralston ; Cumming, Robert ; David, Stuart ; Davidson, Bruce ; Demuth, Charles ; Diller, Burgoyne ; Dine, Jim ; Divola, John ; Dove, Arthur G. ; Eddy, Don ; Eggleston, William ; Estes, Richard ; Evans, Walker ; Faurer, Louis ; Fischl, Eric ; Riverhead (New York) ; Francis, Sam ; Frank, Robert ; Friedlander, Lee ; Gehry, Frank O. ; Goings, Ralph ; Goldberg, Bertrand ; Gorky, Arshile ; Gottlieb, Adolph ; Gropius, Walter ; Guston, Philip ; Halley, Peter ; Hanson, Duane ; Harrison, Wallace K. ; Hart Benton, Thomas ; Hartley, Marsden ; Heinecken, Robert ; Held, Al ; Hesse, Eva ; Hofmann, Hans ; Hopper, Edward ; Howe, George ; Indiana, Robert ; Jahn, Helmut ; Jenney, Neil ; Johns, Jasper ; Johnson, Philip ; Josephson, Kenneth ; Judd, Donald ; Kahn, Louis ; Katz, Alex ; Kelly, Ellsworth ; Klein, William ; Klett, Mark ; Kline, Franz ; de Kooning, Willem ; Kosuth, Joseph ; Krasner, Lee ; Laughlin, Clarence John ; Le Corbusier ; Lescaze, William ; LeWitt, Sol ; Lichtenstein, Roy ; Lindner, Richard ; Longo, Roberto ; Louis, Morris ; Lyon, Danny ; Mangold, Robert ; Marden, Brice ; de Maria, Walter ; Martin, Agnes ; McCollum, Allan ; Meier, Richard ; Metzker, Ray K. ; Meyerowitz, Joel ; Michals, Duane ; Mies van der Rohe, Ludwig ; Model, Lisette ; Moore, Charles ; Morley, Malcolm ; etc.
Bibliog. p. 621-628
Cartografie p. 478-480
Frans
boek
Keywords: U.S.A.; Verenigde Staten